Colonic metastasis from an invasive lobular carcinoma of the breast - Norfaidhi Akram Mat Nor; Samuel T; Norly S; Ros’aini P (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Breast carcinoma to the colon and rectum is rare type of metastatic spread. We report a case of colonic metastasis from a lobular carcinoma of the breast twelve years after the initial diagnosis. Accurate diagnosis and early treatment of systemic therapy can be done if awareness is increased.